Prostate cancer: Quality of life and physical activity level of patients - Silva T.D.* (2018)
© 2018, Universidade Estadual de Maringa.The study examined the relationship between physical activity and quality of life of patients diagnosed with prostate cancer treated at the Oncology Research Center (CEPON). The study involved 85 men with a mean age of 65.9 ± 7.6 years. It made use of a structured questionnaire covering: general information; characteristic of the disease; socioeconomic status (IBGE); physical activity (IPAQ - short version); overall quality of life (QLQ-C30) and; quality of life - prostate cancer (QLQ-PR25). Most indicated to be insufficiently active with a good overall quality of life. There was significance in sub-items of the functional scale, with higher scores in active men, and those who practiced physical activity had fewer symptoms in symptomatic scale. There was a positive correlation between physical activity and quality of life in general and functional scale and items physical and emotional function, and negative in symptomatic scale and nausea items and vomiting, constipation and financial difficulties. In conclusion, the participants were insufficiently active, and the group of assets presented in the functional scale, better physical function, emotional and lower presence of symptoms in symptomatic scale, nausea and vomiting, constipation and financial difficulties, indicative these best quality of life.